Toothpick test: A methodology for the detection of RR soybean plants - da Silva, Fabiana Mota [UNESP]; Unêda-Trevisoli, Sandra Helena [UNESP]; Villela, Otávia Tiago [UNESP]; Perecin, Dilermando [UNESP]; Di Mauro, Antonio Orlando [UNESP] (My University, 2015)
Due to the large increase in the area cultivated with genetically modified soybean in Brazil, it has become necessary to determine methods that are fast and efficient for detecting these cultivars. The aim of this work was to test the efficiency of the toothpick method in the detection of RR soybean plants, as well as to distinguish between cultivars, for sensitivity caused by herbicide. Ten transgenic soybean cultivars, resistant to the active ingredient glyphosate, and ten conventional soybean cultivars were used. Toothpicks soaked in glyphosate were applied to all the plants at stage V6 and evaluations were made at 2, 4, 6, 8 and 10 days after application (DAA). The effects of the glyphosate on the cultivars, and the symptoms of phytotoxicity caused in the transgenic plants were evaluated by means of grading scales. The toothpick test is effective in identifying RR soybean cultivars and also in separating them into groups by sensitivity to the symptoms caused by the glyphosate.
Keywords: Glycine max; Glyphosate; Herbicide; Phytotoxicity; Toothpick method